2023
DOI: 10.3390/healthcare11091274
|View full text |Cite
|
Sign up to set email alerts
|

Procrastination Predicts Future Internet Use Disorders in Adolescents but Not Vice Versa: Results from a 12-Month Longitudinal Study

Abstract: Background: Use of Internet applications is often associated with postponing real-life obligations. Previous cross-sectional studies have reported a positive association between procrastination and Internet use disorders (IUDs). Further, procrastination is included in theoretical models explaining the development of IUDs. However, little is known about the temporal relationship; thus, longitudinal studies identifying the specific predictive direction are required. Methods: Using a cross-lagged panel design, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…On the other hand, procrastination was previously considered a causal factor of PSMU in longitudinal studies [ 63 , 105 ]. According to a survey, 67% of students said that TikTok caused them to procrastinate (e.g., not do homework for school), and 69% of students said they felt addicted to the app [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, procrastination was previously considered a causal factor of PSMU in longitudinal studies [ 63 , 105 ]. According to a survey, 67% of students said that TikTok caused them to procrastinate (e.g., not do homework for school), and 69% of students said they felt addicted to the app [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTTU is associated with spending time on entertainment instead of pursuing important goals, which increases stress and anxiety (because essential goals are not achieved) and ultimately increases depression. People with chronic procrastination, characterized by low self-control levels and a greater tendency to avoid unpleasant activities and duties, can spend more time using social media (including TikTok), which, in turn, could lead to a shift in the precious resource of time and increase procrastination [ 63 , 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…research has shown a positive relationship between GD and procrastination 60,61 which is characterized as "self-regulatory failure of not exerting self-control necessary for task engagement" (p. 116). 62 Here, difficulties for individuals implementing self-control of their behavior (see initiative and persistence self-control dimension) combined with individuals having difficulties in maintaining information about the goals of their actions (see goal maintenance self-control dimension) can both make it easier for gamers to begin a gaming session and harder to end a gaming session.…”
mentioning
confidence: 99%